Calculation and analysis of static errors of two-gyro sensor - Безвесільна, Олена Миколаївна; Ткачук, Андрій Геннадійович; Гуменюк, Анна Анатоліївна; Нечай, Сергій Олексійович (Technology audit and production reserves, 2016)
New two-gyro sensor is considered. It can be used both in automated aviation gravimetric systems, and as the basic measuring device of weapons stabilizer. The object of research is new two-gyro unit (TGU) on the basis of gyro integrator of linear acceleration (GILA). New TGU consists of free gyroscope located in the inner and outer frames with interframe correction systems containing angle sensor on the axis of inner frame of the gyroscope and torque sensor connected to its output. In addition, free gyroscope that identical to the first is included in the design. Rotor of this gyroscope rotates in the opposite direction from the main gyroscope. Additional gyroscope is also provided by similar correction systems. Two output signals of linear acceleration are formed in TGU as the sum of signals from angle sensors of two gyroscopes. Considered TGU provides higher accuracy than single-gyro sensor due to compensation of the errors because of the impact of cross angular velocity and the angular velocity of the Earth.